Barrow of the Early Saka Time Ulkensor - Yarygin Sergey A.; Sakenov Sergazy K.; Mysyr Olzhas D. (Поволжская археология, 2023)
In 2020 on the shore of Lake Ulkensor (in the Burabay district of the Akmola region) a single barrow was discovered and then studied, there was a burial of the early Saka time. This paper presents an analysis of the results of a practical study of the obtained materials and their interpretation. The burial was performed in undercut, at the bottom there was a full skeleton of a man in an extended position, on his back, with his head oriented to the west with a deflection to the south. Accompanying goods are represented by a composite belt, a bronze dagger in a case with a chape, a grindstone, a quiver with bronze arrowheads, a whip, a antler clasp and an iron knife. The burial rite and set of items allow the authors to attribute the site to the Ulubai-Tasmola archaeological culture of Northern Kazakhstan and date it to the 7th–6th centuries BC. The most important archaeological find for the region is a composite belt, its details are made of antler (presumably, of deer antler). The shape and type of individual elements of this specific decoration, its decor and design features reflected the position of the owner on the social ladder and also find analogies in the Tasmola culture of Central Kazakhstan and in the circle of early Saka sites from the Urals to the Altai-Sayan.